Myeloproliferative neoplasms and inflammation: whether to target the malignant clone or the inflammatory process or both - Koschmieder, Steffen; Hehlmann, Rüdiger (Leukemia, 2016)
The Philadelphia-negative myeloproliferative neoplasms (MPNs) are clonal disorders involving hematopoietic stem and progenitor cells and are associated with myeloproliferation, splenomegaly and constitutional symptoms. Similar signs and symptoms can also be found in patients with chronic inflammatory diseases, and inflammatory processes have been found to play an important role in the pathogenesis and progression of MPNs. Signal transduction pathways involving JAK1, JAK2, STAT3 and STAT5 are causally involved in driving both the malignant cells and the inflammatory process. Moreover, anti-inflammatory and immune-modulating drugs have been used successfully in the treatment of MPNs. However, to date, many unresoved issues remain. These include the role of somatic mutations that are present in addition to JAK2V617F, CALR and MPL W515 mutations, the interdependency of malignant and nonmalignant cells and the means to eradicate MPN-initiating and -maintaining cells. It is imperative for successful therapeutic approaches to define whether the malignant clone or the inflammatory cells or both should be targeted. The present review will cover three aspects of the role of inflammation in MPNs: inflammatory states as important differential diagnoses in cases of suspected MPN (that is, in the absence of a clonal marker), the role of inflammation in MPN pathogenesis and progression and the use of anti-inflammatory drugs for MPNs. The findings emphasize the need to separate the inflammatory processes from the malignancy in order to improve our understanding of the pathogenesis, diagnosis and treatment of patients with Philadelphia-negative MPNs.
Gesehen am 08.05.2019